2015
DOI: 10.1039/c5tb00714c
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of human mesenchymal stem cells on biomineralized conducting polymers enhances their differentiation towards osteogenic outcomes

Abstract: Tissue scaffolds allowing the behaviour of the cells that reside on them to be controlled are of particular interest for tissue engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 85 publications
0
24
0
Order By: Relevance
“…As an alternative, MSCs with self-renewing abilities can differentiate into chondrocytes and offer a reliable resource for ES-based therapies for damaged cartilage defects. However, although recent studies have reported the effects of ES on proliferation and differentiation of MSCs3637, it remains unclear whether ES induces chondrogenic differentiation of MSCs.…”
mentioning
confidence: 99%
“…As an alternative, MSCs with self-renewing abilities can differentiate into chondrocytes and offer a reliable resource for ES-based therapies for damaged cartilage defects. However, although recent studies have reported the effects of ES on proliferation and differentiation of MSCs3637, it remains unclear whether ES induces chondrogenic differentiation of MSCs.…”
mentioning
confidence: 99%
“…8 In this research, we attempted to evaluate their possible functional synergism for bone tissue engineering. 8 In this research, we attempted to evaluate their possible functional synergism for bone tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, direct stimulation, capacitive-coupling, and inductive-coupling methods were utilized to deliver electrical stimulus with dissimilar effects on osteoblasts and mesenchymal stem cells. [7][8][9][10][11][12][13] Among conductive polymers, polypyrrole, polyaniline, and polythiophenes have been extensively utilized in biomedical engineering as biosensors, neural probes, tissue engineering scaffolds, drug delivery carriers, and so on. On the other hand, inductive-coupling inhibited cell growth and enhanced mineralization and expression of BMP-2 and transforming growth factor beta 1 (TGFb-1).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effect of cell interaction with an electrically active substrate based on CPs has been well documented on cell growth, attachment and proliferation, as well as control of cell migration and protein conformation . More recently CPs are being used to manipulate the properties of stem cells through electrical or photostimulation .…”
Section: Conjugated Polymers Tested In Vivomentioning
confidence: 99%